OPTIMASI FORMULA MATRIKS KITOSAN DENGAN METILSELULOSA PADA PELEPASAN TERKENDALI SEDIAAN GRANUL TEOFILIN - Suprianto Suprianto (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
The in vitro study was carried out on the release of active ingradient theophylline from granules prepared by moist granulation method. The granule matrix was prepared from the mixture of chitosan isolated from SwaIIo shrimp (Metapenaeus monoceros) (in accordance with the Protan Laboratories, Inc standard requirement) and methylceliuiose 1500 cps. The granules were filled into 850 mg capsules containing 200 mg theophylline. The maximum weight of chitosan and methylcellulose for each capsule was determined by factorial design 22.The result showed that, when the amount of chitosan was kept constant, an increase in the amount of methylcellulose will increase the release rate of theophylline from granules. The optimum weight of chitosan and methyIceIIuIose are 609.24 mg and 20.00 mg, respectively for one capsule.